Perovskite Solar Cells: Effect of the Microstructure of the Functional Layers on the Efficiency of Perovskite Solar Cells (Adv. Mater. 20/2017). Issue 20 (May 2017) - Huang, Fuzhi; Pascoe, Alexander R.; Wu, Wu‐Qiang; Ku, Zhiliang; Peng, Yong; Zhong, Jie; Caruso, Rachel A.; Cheng, Yi‐Bing
Abstract : Pinhole‐free, dense perovskite films with large grains, which can be achieved by control of the nucleation and crystal growth, are essential for high‐performance perovskite solar cells. These perovskite‐solar‐cell systems are discussed by Fuzhi Huang, Yi‐Bing Cheng, and co‐workers in article number1601715 .